Factors Influencing the Development of Archaeological and Religious Tourism in Samarra - Asst.Lecte.sabah shukur mahmood (Journal of College of Education, 2025)
This research examines "the factors contributing to the development of archaeological and religious tourism and their impact on enhancing tourism activity in Samarra," by analyzing the most prominent determinants affecting the reality of religious and archaeological tourism in the city. It seeks to identify the challenges and available potential, and to determine the roles of official bodies, the local community, and tourism and religious institutions in supporting the tourism sector. The research relied on a descriptive and analytical approach, employing tools such as interviews with stakeholders and analysis of official documents and academic sources. It concluded that there are key factors controlling the course of tourism development, most notably: infrastructure, the security environment, tourism marketing, and community awareness. The research proposes a set of recommendations that would contribute to revitalizing archaeological and religious tourism in Samarra, if implemented in a thoughtful and integrated manner.